Prudential regulations for greening the financial system: Coping with climate disasters - Daniel M. Schydlowsky (Latin American Journal of Central Banking (LAJCB), 2020)
Prudential financial regulators, central banks, and regulatory authorities have increasingly come to recognize that they have a role to play in dealing with climate change, including climate disasters such as storms, tornados, tsunamis, and so on. Such climate events impact the real economy by destroying physical assets, income opportunities, credit worthiness, and the fiscal base. In turn, the financial system is impacted by destruction of collateral and of the ability to pay, an increase in defaults, required insurance payouts, and a flip in the fiscal balance. Regulators' policy options can usefully be classified into those that provide direct support, promote supporting responses by the system, protect from the effects, and prevent the consequences as much as possible. Regulators also have a role to play in turning prospective (and past) climate disasters into an advantage by inducing assets to become more resistant in the face of climate change, supporting technological change, and supporting behavioral change. Specific regulatory policy toward climate disasters involves some general climate change-related regulations, such as requiring improved building codes for writing mortgages, but also includes prepositioning regulations to become activated in the climate emergency and a second set to become activated in the recovery period. Fortunately, the regulatory instruments involved are all well within the current established practice.
Keywords: 330